METHODS OF TEACHING FUNCTIONAL STATES OF THE ORGANISM AND DEFENSIVE-ADAPTIVE PROCESSES THROUGH MATHEMATICAL MODELING IN MEDICAL EDUCATION (Scientific journal of the Fergana State University, 2025)
The article presents an analysis of modern approaches to improving the effectiveness of education in medical education through mathematical modeling of functional states of the organism and protective-adaptive processes. The study emphasizes the need for a systematic study of the basic biophysical mechanisms of physiological and adaptive processes in order to develop students' understanding and practical application skills. By integrating mathematical modeling, students gain a deeper understanding of the dynamic processes of the human body and develop critical thinking and problem-solving skills that are important for future medical practice. The proposed mathematical modeling methods allow studying the levels of adaptation and health of the organism, developing education based on systematic and expanded integration into medical curricula, and bridging the gap between theoretical knowledge and practical application for students.